Studi Sistem Konversi Panas Buang Konduksi Berbasis Termoelektrik Generator - Risse Entikaria Rachmanita (Jurnal Teknologi Terpadu, 2020)
Thermoelectric generator (TEG) is an electrical generator device that converts temperature differences into electrical energy directly. Based on the Seebeck effect, if two different metals are connected at one end, then a temperature difference is given at the joint, there will be a difference in voltage between one end and the other. The purpose of this research is to create a conversion system based on thermoelectric generator (TEG) that utilizes the conduction heat of the biomass furnace when used for cooking, so that it can also be used as a power plant. This study used two TEG SP1846 peltiers with test variation used one TEG, two TEGs in series connection and twoTEGs in parallel connection. The results showed that the conduction heat conversion system of biomass furnace using 300 gr of sengon wood and two TEGs connected in series could produce a temperature on the hot side of the TEG maximum of 153.1oC and the temperature on the cold side of the maximum TEG of 106.4 oC. So that, the maximum voltage value of 7.19 volts and a maximum current of 0.023A and a power of 0.16537 watts.